Assessment of Use of Arteriovenous Graft vs Arteriovenous Fistula for First-time Permanent Hemodialysis Access - Hicks, Caitlin W. (JAMA Surg, 2019)
IMPORTANCE: Initial hemodialysis access with arteriovenous fistula (AVF) is associated with superior clinical outcomes compared with arteriovenous graft (AVG) and should be the procedure of choice whenever possible. To address the national underuse of AVF in the United States, the Centers for Medicare & Medicaid has established an AVF goal of 66% or greater in 2009. OBJECTIVE: To explore contemporary practice patterns and physician characteristics associated with high AVG use compared with AVF use. DESIGN, SETTING, AND PARTICIPANTS: This review of 100% Medicare Carrier claims between January 1, 2016, and December 31, 2017, includes both inpatient and outpatient Medicare claims data. All patients undergoing initial permanent hemodialysis access placement with an AVF or AVG were included. All surgeons performing more than 10 hemodialysis access procedures during the study period were analyzed. EXPOSURES: Placement of an AVF or AVG for initial permanent hemodialysis access. MAIN OUTCOMES AND MEASURES: A surgeon-level AVG (vs AVF) use rate was calculated for all included surgeons. Hierarchical logistic regression modeling was used to identify patient-level and surgeon-level factors associated with AVG use. RESULTS: A total of 85 320 patients (median age, 70 [range, 18-103] years; 47 370 men [55.5%]) underwent first-time hemodialysis access placement, of whom 66 489 (77.9%) had an AVF and 18 831 (22.1%) had an AVG. Among the 2397 surgeons who performed more than 10 procedures per year, the median surgeon level AVG use rate was 18.2% (range, 0.0%-96.4%). However, 498 surgeons (20.8%) had an AVG use rate greater than 34%. After accounting for patient characteristics, surgeon factors that were independently associated with AVG use included more than 30 years of clinical practice (vs 21-30 years; odds ratio, 0.85 [95% CI, 0.75-0.96]), metropolitan setting (odds ratio, 1.25 [95% CI, 1.02-1.54]), and vascular surgery specialty (vs general surgery; odds ratio, 0.77 [95% CI, 0.69-0.86]). Surgeons in the Northeast region had the lowest rate of AVG use (vs the South; odds ratio, 0.83 [95% CI, 0.73-0.96]). First-time hemodialysis access benchmarking reports for individual surgeons were created for potential distribution. CONCLUSIONS AND RELEVANCE: In this study, one-fifth of surgeons had an AVG use rate above the recommended best practices guideline of 34%. Although some of these differences may be explained by patient referral practices, sharing benchmarked performance data with surgeons could be an actionable step in achieving more high-value care in hemodialysis access surgery.